Pengaruh Sistem Tanam dan Pemupukan N, P. Dan K terhadap Sifat Fisika Tanah dan Hasil Beberapa Tanaman Palawija pada Lahan Terkena Tsunami - Ainun Marliah (Fakultas Pertanian, Universitas Syiah Kuala, 2009)
The Effects of Some Cropping Systems and N, P, K Fertilizer to Physical Properties of Soil and Land Equivalent Ratio at Tsunami Affected LandABSTRACT. The aim of study to know the effects of some cropping systems and N, P, K fertilizer as well as the interaction of both factors to improve soil productivity and land equivalent ratio at tsunami affected land in Aceh Besar, Indonesia. The experimental design was Block Randomized Design with two factors and two replications. The first factor was cropping systems; those were maize monoculture, green bean monoculture, groundnut monoculture, maize-green bean intercropping and maize-groundnut intercropping. Then the second factor was level of N, P, K fertilizer, those were control, low dose (90 kg ha-1 N, 35 kg ha-1 P2O5, 20 kg ha-1 K2O) and high dose (180 kg ha-1 N, 70 kg ha-1 P2O5, 40 kg ha-1 K2O). The observation was done for physical properties of soil and land equivalent ratio. The result showed that the lowest soil weight was obtained from maize-green bean intercropping and maize groundnut intercropping. The highest soil permeability was found in maize-groundnut intercropping. Maize-green bean intercropping using high fertilizer dose gave the highest land equivalent ratio (1,96).